2021
DOI: 10.3390/s21227430
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Biosensors for Meat Quality Evaluations

Abstract: The aim of this study was to apply biosensors in the assessment of meat quality. The research was carried out on 20 samples of the Longissimus muscle obtained from pork of Polish Landrace and Polish Large White hybrids of fattening pigs. In the samples, 48 h after slaughter pH values, color parameters in the CIE system (L* a* b*), the volume of natural drip loss and intramuscular fat content were measured. The commercially available biosensor Accutrend Plus was used to measure glucose, triglycerides and lactic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Fermented feed had a significant effect on improving the sensory quality of pork, including pH value, meat color, marbling scores, shear force, water‐holding capacity, and flavor substances, which are closely related to meat quality and consumer acceptability (Zhang, Li, et al, 2022). It is found that glucose content had a significant negative correlation with the pH in pork (Sionek et al, 2021). Moreover, meat color is one of the most important characteristics of fresh meat, and redder meat is more popular in China, which is consistent with the results of increased a* value in fermented feed in Table 1, leading to the improved quality of meat.…”
Section: Effects and Regulatory Mechanism Of Fermented Feed On Pork Q...mentioning
confidence: 99%
“…Fermented feed had a significant effect on improving the sensory quality of pork, including pH value, meat color, marbling scores, shear force, water‐holding capacity, and flavor substances, which are closely related to meat quality and consumer acceptability (Zhang, Li, et al, 2022). It is found that glucose content had a significant negative correlation with the pH in pork (Sionek et al, 2021). Moreover, meat color is one of the most important characteristics of fresh meat, and redder meat is more popular in China, which is consistent with the results of increased a* value in fermented feed in Table 1, leading to the improved quality of meat.…”
Section: Effects and Regulatory Mechanism Of Fermented Feed On Pork Q...mentioning
confidence: 99%
“…Furthermore, most of these methods necessitate lengthy sample preparation and processing steps that involve various enrichment and incubation stages, and can take up to 10 days to produce results [61][62][63]. These limitations have created a demand for novel in situ analysis methods that are more sensitive, accurate, fast, and specific than existing methods [7,14,64]. Recently, analytical tools like biosensors with high specificity and sensitivity have become available, which can detect microbiological safe limits, toxins, or their metabolites in different products.…”
Section: Biosensors To Detect Microbial Contaminants In Meatmentioning
confidence: 99%
“…Furthermore, different types of nanomaterials, such as carbon nanotubes, graphite, and graphene, with a high surface area and several available active sites, may provide added biocompatibility to these sensors. In the near future, these advanced nano biosensors may play a crucial role in the rapid and accurate detection of any kind of physical, chemical, or microbiological hazards in meat preservation systems [7,8]. Although many articles on biosensors have been published recently, an updated and comprehensive review on the usefulness of biosensors in meat and meat products is highly desired.…”
Section: Introductionmentioning
confidence: 99%